Annual and monthly range fidelity of female boreal woodland caribou in respons to petroleum development - Tracz, Boyan V.; LaMontagne, Jalene M.; Bayne, Erin M.; Boutin, Stan (Rangifer, 2010)
Petroleum-sector development in northern Alberta, Canada has been implicated as one factor influencing the decline of boreal woodland caribou (Rangifer tarandus caribou). Previous research showed that caribou are farther from petroleum-sector disturbances within their home range than expected. As petroleum development increases, the distance caribou can selectively place themselves relative to industrial disturbance must decrease, because distances between disturbances decrease. Conceptually, the number of local disturbances becomes so large that caribou either abandon their local avoidance behaviour or leave their traditional home range. We evaluated whether an intense petroleum- development event in northern Alberta was sufficient to result in home range abandonment by female woodland caribou. Using well locations as an index of petroleum development, we found that caribou studied from 1992 to 2000 did not change their annual or monthly range fidelity as a function of development intensity. Caribou remained in peatland complexes containing a large number of petroleum-sector disturbances rather than move to new areas, presumably because the risks of dispersing across upland habitat to reach other suitable habitat are high. Such range fidelity may have fitness consequences for woodland caribou if they suffer greater predation in areas where petroleum development is occurring.